Late-Onset Aspergillus Fumigatus Infection of an Aortic Stent Graft in an Immunocompetent Patient - Ballazhi, Fatos; Weyand, Michael; Lang, Werner; Schoerner, Christoph; Seitz, Timo (The Thoracic and Cardiovascular Surgeon Reports, 2015)
Aspergillus fumigatus as a clinical entity is difficult to diagnose. We present a case, which could facilitate diagnosis and management of the aforementioned disease. A 60-year-old man with stent graft implantation in the descending aorta (6 years ago) presented with fever, night sweats, and weight loss over 5 months. Leukocytosis and elevated C-reactive protein were constantly spiking. Blood cultures were negative. Notably, the serum immunoglobulin E (IgE) level was strongly elevated (> 1,000 U/mL). Anamnestically, the patient suffered from a mild form of atopic dermatitis and bronchial asthma. The pulmonary status showed no abnormalities in the computed tomography image. Nonetheless, a chest scan revealed a suspected abscess around the stent graft of the descending aorta. Extra-anatomic ascending to descending aortic bypass (Gelsoft 22 mm, Vascutek, Juchinnan, Scotland, United Kingdom) was performed. Intraoperative samples revealed A. fumigatus. These findings were confirmed by polymerase chain reaction analysis. Infection by A. fumigatus represents a diagnostic challenge because blood cultures are usually negative, but expeditious treatment is required to prevent occurrence of irreversible complications. A late graft infection, possibly caused by A. fumigatus should be suspected in patients with implanted grafts, who suffer from unexplained, blood culture-negative fever that does not respond to antibiotics and who have a history of dermatitis or bronchial asthma with elevated IgE antibodies.
Keywords: graft infection; aorta; Aspergillus fumigatus